Vocational training in soy-based food production for persons with mental retardation - Aguilar, Emeruth Habacon (2007)
The performance of ten persons with mild to moderate mental retardation in soymilk, taho and tofu production was evaluated in this experimental study using a researcher-designed instructional module as intervention tool during training. Pretest and posttest results were compared using two tailed paired t-test. There were significant differences in their performance in soymilk, taho and tofu production before and after vocational training. Based on the statistical results and constant increase in scores during training, the module is an effective source of instruction.
Thesis (M.A. Special Education)--University of the Phillipines, Diliman.
Keywords: People with mental disabilities -- Education -- Philippines -- Quezon City; People with mental disabilities -- Employment -- Philippines -- Quezon City; Vocational education -- Philippines -- Quezon City; Special education -- Philippines -- Quezon City